THE IMPACT OF ORGANIZATIONAL CLIMATE ON BUSINESS PERFOMANCE IN LAGOS METROPOLIS - Abayomi Olarewaju Adeoye; Ibukun Olorunisola Kolawole; Ayobami Folarin Elegunde; Olajide Clement Jongbo (European Scientific Journal, ESJ, 2014)
The objective of the paper is to have a critical look at the impact of organizational climate on business performance in Lagos metropolis. The business performance is a function of the of the people within an organization and their environment i.e. B.P=F (PxE). Relevant literatures were reviewed. The paper adopted empirical study by using some organizations through administration of 150 structured questionnaires while 120 were returned. The findings of the paper is that good organizational climate is necessary to achieve goals of the organization and that there is a significant relationship between organizational climate and business performance.